Isopycnal Eddy Stirring Dominates Thermohaline Mixing in the Upper Subpolar North Atlantic - Fernández Castro, Bieito; Fernandez Roman, Daniel; Ferron, Bruno; Fontela, Marcos; Lherminier, Pascale; Naveira Garabato, Alberto C.; Pérez, Fiz; Pranas Spingys, Carl; Polzin, Kurt; Velo, Anton (Journal of Geophysical Research: Oceans, 2024)
The Atlantic Meridional Overturning Circulation (AMOC) entails vigorous thermohaline transformations in the subpolar North Atlantic (SPNA). There, warm and saline waters originating in the subtropics are converted into cooler and fresher waters by a combination of surface fluxes and sub-surface thermohaline mixing. Using microstructure measurements and a small-scale variance conservation framework, we quantify the diapycnal and isopycnal contributions to thermohaline mixing within the eastern SPNA. Isopycnal stirring is found to account for 65% of thermal and 84% of haline variance dissipation in the upper 400 m of the eastern SPNA, suggesting an important role of isopycnal stirring in regional water-mass transformations. By applying the tracer variance method to two tracers, we underscore the special significance of isopycnal stirring for tracers weakly coupled to density, such as biologically-active tracers. Our findings thus highlight the central role of isopycnal stirring in both the AMOC and biogeochemical dynamics within the SPNA.